Identifying and addressing employment barriers in Belgium, Korea and Norway Implementing the OECD Jobs Strategy - Fernandez, Rodrigo (OECD Social, Employment and Migration Working Papers, 2020)
This paper documents joblessness in OECD countries, provides a detailed diagnosis of structural employment barriers in Belgium, Korea and Norway by applying the OECD Faces of Joblessness methodology to the situation just before the COVID-19 crisis and discusses the policy implications. It shows that individuals experiencing major employment difficulties often face a combination of barriers related to work availability, readiness and incentives. It suggests a number of avenues for enhancing the effectiveness of public support: i) make greater use of statistical profiling tools to adapt programmes to the needs of the jobless and target resources to those at the highest risk of long-term joblessness; ii) better coordinate support provided by employment, health and education services; iii) place a greater emphasis on preventive policies (equal opportunities, life-long learning)